“Pineapple eyes”: local social networks to prevent and control epidemics in Thailand’s southern beach tourism provinces - Jitwarin, Lapasrada; Chinabhark, Krittabhart; Jitwarin, Tawatchai (International Journal of Public Health Science (IJPHS), 2025)
The study aimed to qualitatively examine epidemic prevention and control processes in beach tourism provinces in the upper southern region of Thailand, as well as investigate networks related to public health emergency management (PHEM) during such epidemics. The findings highlighted key elements of PHEM for emerging infectious diseases. This involved initial assessments of epidemics and health conditions, categorizing the population by risk, and performing prognosis. Subsequently, operational guidelines for prevention, disease control, and treatment were proposed and often submitted for consideration and orders to the provincial communicable disease control committee. Meetings were held to disseminate committee announcements and measures for implementation by relevant departments, enhancing operational guideline development. Successful local networks as pineapple eyes for PHEM in response to emerging infectious diseases were characterized by robust social networks and informal cooperation at village and community levels, serving as crucial mechanisms for disease control and care. Additionally, business sector networks transformed "mutual suffering" into cooperation, with entrepreneurs in the tourism industry taking the lead. They developed various websites and applications at different stages to promote and support situation management, proving to be a vital mechanism for an effective response to emerging infectious diseases.